Environment Fettle by the Exposure of Electromagnetic Radiation - Suryandari Suryandari (ESE International Journal (Environmental Science and Engineering), 2019)
The use of technology in the industrial era 4.0 switched to wireless technology and is commonly called the Internet of Things (IoTs). Wireless technology relies on an RFR intensity basis that has biological effects on humans depending on how much energy is absorbed by living things (SAR) in the infrastructure environment such as in wireless transmission areas for television, radio, internet, and so on. RFR effects are generally known as electromagnetic radiation (EMR) which in long-term use can cause health complaints to the surrounding environment both physiological and psychological effects even though the SAR is known below the safe threshold. The impact of EMR on the environment is spread to all elements namely to humans, animal, and plants. Although several studies are showing the benefits of EMR on the environment, this needs to be further tested because the history of EMR in the past always has a negative impact, especially on the health aspect. The EMR countermeasure itself has been carried out to minimize the SAR level of the environment in an intelligible manner. This is a big job for humanity because EMR is formed from the technology of human creation itself